2016
DOI: 10.1007/s00360-016-1013-1
|View full text |Cite
|
Sign up to set email alerts
|

Changes of hemoglobin expression in response to hypoxia in a Tibetan schizothoracine fish, Schizopygopsis pylzovi

Abstract: Fishes endemic to the Qinghai-Tibetan Plateau are comparatively well adapted to aquatic environments with low oxygen partial pressures (hypoxia). Here, we cloned the complete cDNA of hemoglobin (Hb) α and β from the Tibetan schizothoracine fish Schizopygopsis pylzovi, and then investigated changes in Hb mRNA and protein levels in spleen, liver and kidney in response to hypoxia. We applied severe hypoxia (4 h at PO = 0.6 kPa) and moderate hypoxia (72 h at PO = 6.0 kPa) to adult S. pylzovi. Changes of Hb express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…It has been previously hypothesized that species with multiple Hbs acting in concert would be better suited to tolerate environmental perturbation 1 , 30 – 32 ; however, the physiological support for this is mixed 6 , 7 , 10 , 30 . But previous work has primarily focused on temperature, with relatively less work focusing on prolonged hypoxia acclimation 3 , 5 , 33 , 34 . Here we provide evidence that specific Hb isoforms are selectively up-regulated in response to hypoxia stress, which is also correlated with a decrease in hemolysate P 50 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously hypothesized that species with multiple Hbs acting in concert would be better suited to tolerate environmental perturbation 1 , 30 – 32 ; however, the physiological support for this is mixed 6 , 7 , 10 , 30 . But previous work has primarily focused on temperature, with relatively less work focusing on prolonged hypoxia acclimation 3 , 5 , 33 , 34 . Here we provide evidence that specific Hb isoforms are selectively up-regulated in response to hypoxia stress, which is also correlated with a decrease in hemolysate P 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The freshwater in the tanks was bubbled with nitrogen and with the ambient air in our laboratory. The dissolved oxygen (DO) level was continuously monitored using an AZ8402 dissolved oxygen meter (AZ Instrument Corp., Taiwan) ( Xia et al, 2016 ). In the normoxia (control) tank, DO was 8.4 ± 0.1 mg/L.…”
Section: Methodsmentioning
confidence: 99%
“…The schizothoracine fish are divided into three groups based on morphological characters: primitive, specialized, and highly specialized ( Cao et al, 1981 ). Previous studies have demonstrated that schizothoracine fish restricted to high-altitude or high-latitude environments are well adapted to cold, hypoxic conditions ( Qi et al, 2012 ; Li et al, 2013 ; Guan et al, 2014 ; Xia et al, 2016 ). Therefore, the schizothoracine fish are an excellent model for studies of the fundamental mechanisms of adaptions to hypoxia and low temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations